WTO negotiations on agriculture and developing countries - Hoda, Anwarul; Gulati, Ashok (International Food Policy Research Institute, 2008)
For more than six years the trade talks of the World Trade Organization (WTO) have been stalled, mainly on account of differences in countries' levels of ambition for reducing support to and protection of agriculture. The expiration of the U.S. president's trade negotiating authority on June 30, 2007, raised the prospect of longer delay. More recently, however, the unprecedented food crisis may have created an environment for reducing the divergences in countries' negotiating positions, and efforts for agreement have intensified at Geneva. To aid developing-country negotiators, the book WTO Negotiations on Agriculture and Developing Countries (published for IFPRI by the Johns Hopkins University Press and Oxford University Press-India) offers the first authoritative analysis of the rules and modalities on which governments of developing countries can rely and suggests a negotiating strategy for developing countries.